Cognitive-behavioral therapy as an important component of complex treatment of sleep disorders in somatoform disorders - Plevachuk Оксана; Rakhman Людмила; Shpyl’ovyj Ярослав (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is devoted to the analysis of the effectiveness of cognitive-behavioral therapy in the complex treatment of sleep disorders in somatoform disorders.